Mixed signals from Kerala's improving health status - Michael, EJ and Singh, B (The Journal of The Royal Society for the Promotion of Health; March 2003, 123 (1), pp. 33-38, 2003)
It can be said that health policy is about creating the conditions to free a population from disease and impairment, and so prolong the quality of life for all. If this is its purpose, then the practice of public health policy in the Indian state of Kerala presents a conundrum for health promotion analysts. On the one hand,Kerala has had remarkable success in reducing its infant mortality rates to around one-third of the Indian average, but on the other, its morbidity rates have risen to impose an economic cost more than three times the national level. This paper sets out to explain this apparent contradiction in outcomes, serving both to provide a review of Kerala.s health status and as an illustrative guide for the interpretation of the effects of health policy in some other developing areas. While the essential health data for Kerala might imply an unsatisfactory future, the authors argue that the rapid improvements that have occurred simultaneously in public education are more likely to explain an increase in the effective reporting of disease conditions, thus suggesting a more optimistic scenario for future practice that can lead to a sustained improvement in health care.